Toxoplasmosis in pregnancy: test, treatment and outcome - Kaya Kalem, Ayşe; Hasanoğlu, İmran; Ayhan, Müge; Kayaaslan, Bircan; Eser, Fatma; Oğuz, Yüksel; Avşar, Filiz; Güner, Rahmet (The European Research Journal, 2022)
Objectives: The aim of this study was to share the results, follow-up, and treatment characteristics of our pregnant women who were followed-up with anti-Toxoplasma gondii Immunoglobulin (Ig) M positivity during pregnancy. Methods: Anti-T. gondii IgM- and IgG-positive pregnant women were evaluated between 2014-2018. Demographic characteristics, treatment, and information about pregnancy were obtained from the electronic database. Pregnant women were divided into three groups; primary infection, no infection, and suspected infection in pregnancy. Primary and suspected infection in pregnancy were followed up congenital toxoplasmosis risky pregnancy. Fetal ultrasonography (USG), T. gondii DNA polymerase chain reaction (PCR) result in amniotic fluid were recorded. Results: Twenty-four pregnant women with a mean age of 27.9 years were followed up. IgG avidity results were low in 37.5% (n = 9), intermediate avidity in 8.3% (n = 2), and high avidity in 54.2% (n = 13) of pregnant women. Eleven (45.9%) pregnant women had congenital toxoplasmosis risky pregnancy. Fetal USG was performed on ten pregnant women, and no signs of congenital toxoplasmosis were found. Amniocentesis was performed in 72.7% (n = 8) of the participants, and the amniotic fluid T. gondii DNA-PCR result was negative in all of them. Ten (90.9%) pregnancies resulted in mature birth and one (9.1%) resulted in miscarriage. Conclusions: Anti-T. gondii IgM positivity is an indication of acute infection. But IgM can persist for years, and be false-positive in pregnancy. Therefore, additional tests are required, and leading to emotional distress and unnecessary interventions in pregnacy women. These results can aid in developing an approach to screening and diagnosis of T. gondii infection in pregnancy.